Impact of Dural Resection on Sinonasal Malignancies with Skull Base Encroachment or Erosion - Ziai, Hedyeh; Yu, Eugene; Fu, Terence; Muhanna, Nidal; Monteiro, Eric; Vescan, Allan; Zadeh, Gelareh; Witterick, Ian J.; Goldstein, David P.; Gentili, Fred; de Almeida, John R. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objectives (1) To determine the occult rate of dural invasion in patients with tumors extending to and/or eroding the bony anterior skull base but without evidence of dural invasion on preoperative imaging. (2) To determine the impact of dural resection and of skull base erosion on survival outcomes in this group of patients (without evidence of dural invasion upon preoperative imaging).Study Design Retrospective study.Setting Tertiary care academic center.Participants Patients with sinonasal malignancies with anterior skull base encroachment/erosion without dural invasion on preoperative imaging treated surgically.Main Outcome Measures (1) Histopathologic disease in the dura in patients who had dural resection and (2) Oncologic outcomes (5-year local recurrence, dural recurrence, disease-specific survival, and overall survival) in patients with and without dural resection, and patients with and without skull base erosion.Results Thirty-seven patients were included. The occult rate of dural invasion was 54%. Patients with dural resection had improved margin control versus those without dural resection (90% vs 56%, p = 0.02). Dural resection improved 5-year overall survival only in patients with esthesioneuroblastoma compared with bony skull base resection alone (100% vs 75%, p = 0.03). Patients with skull base erosion had reduced local control versus those without erosion (63% vs 93%, p = 0.047).Conclusion This study suggests a substantial rate of occult dural invasion despite no overt imaging findings. Dural resection may be associated with improved margin control, but no oncologic benefit except for esthesioneuroblastomas, although treatment heterogeneity and small sample size may limit conclusions.
Keywords: nose and paranasal sinuses (head and neck); skull base (head and neck); radiology; survival